تقييم قابلية نوعين من قواقع المياه العذبة على مراكمة بعض العناصر في كتلتها الحية والاصداف - مفيد قاسم محمد ابو تراب; عماد هادي محسن القاروني; حامد طالب السعد (مجلة علوم ذي قار, 2019)
The ability of snails Melanopsis nodosa and Lymnaea auricularia has been estimated on bioaccumulation for Zn, Al, Li, V, Ce and P in soft tissue and shell. Significant correlation for Zn, Al and P concentration was found in both species. The amount and ability of bioaccumulation for all elements in the two species were convergent except for Al it was in L. auricularia higher than M. nodosa more than four times. The concentrations of Zn, Al, V, Ce in soft tissue were higher than shell in both species except Li it was high in L. auricularia shell in comparison with the soft tissue. The elements followed this order P < Al < Zn < V < Li < Ce in soft tissue and shell except for L. auricularia shell in which Al concentration is more than P.